2008
DOI: 10.1111/j.1471-0307.2008.00400.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of traditional Croatian ewe's cheese from the island of Krk

Abstract: Krk cheese is a hard, full‐fat cheese made from raw sheep's milk, characterized by a delicate, full and strong flavour. The aim of this study was to determine farm influence on the chemical composition of sheep's milk for Krk cheese production, and the chemical characteristics of Krk cheese during ripening. Gross composition of the milk used complies with the average sheep's milk composition from the Croatian Adriatic region. During ripening, fat, protein, salt content and lactic acid concentration increased (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…These proteolytic changes caused a significant increase (P < 0.05) of Index betta ( Figure 5). Similar results were obtained by other authors who observed that plasmin is a key enzyme in the ripening of some cheeses produced from raw ewe's milk such as Krk or Istrian cheese (Mikulec et al, 2008;Magdić et al, 2013) or from raw cow's milk such as Tounj cheese (Kalit et al, 2005). α s1 -casein could be an indicator of the maturity of Livanjski cheese while the ratio β-casein : α s1 -casein at the end of ripening was 1.46.…”
Section: Resultssupporting
confidence: 76%
“…These proteolytic changes caused a significant increase (P < 0.05) of Index betta ( Figure 5). Similar results were obtained by other authors who observed that plasmin is a key enzyme in the ripening of some cheeses produced from raw ewe's milk such as Krk or Istrian cheese (Mikulec et al, 2008;Magdić et al, 2013) or from raw cow's milk such as Tounj cheese (Kalit et al, 2005). α s1 -casein could be an indicator of the maturity of Livanjski cheese while the ratio β-casein : α s1 -casein at the end of ripening was 1.46.…”
Section: Resultssupporting
confidence: 76%
“…; Mikulec et al . ). It is produced from ewe's milk collected at the local farms which breed Croatian autochthonous sheep – pramenka (Zdanovski ).…”
Section: Introductionmentioning
confidence: 97%
“…; Mikulec et al . ). Krk cheese is made wholely of a raw ewe's milk, using starter culture consisting of Lactococcus lactis subsp.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations